Pembingkaian Narasi Media Massa Terkait Dugaan Manipulasi Pemilu 2024 - Nabilah Azzahra; Filia (Faculty of Social Science, Universitas Negeri Malang, 2024)
This study aims to analyze the framing of mass media narratives regarding the alleged manipulation of the 2024 Election, revealed through the research data source, namely the documentary film Dirty Vote and the TV program Bocor Alus Politik titled “Hak Angket Kecurangan Pemilu VS Tawaran Kursi Menteri Prabowo-Gibran” and